Spin–orbit torque induced magnetization switching in Pt/Co/Ta structures with perpendicular magnetic anisotropy. (5th September 2017) - Yun, Jijun; Li, Dong; Cui, Baoshan; Guo, Xiaobin; Wu, Kai; Zhang, Xu; Wang, Yupei; Zuo, Yalu; Xi, Li
Abstract: Spin–orbit torque (SOT) induced magnetization switching is investigated in Pt/Co/Ta stacks with perpendicular magnetic anisotropy with the variation of the thickness of Ta layer ( t Ta ). SOT is characterized by an effective spin Hall angle θ SH, which is determined by an anomalous Hall resistance measurements method based on a macrospin model. A high charge current induced magnetization switching efficiency is achieved by the enhanced injection efficiency of spin currents from bottom Pt and top Ta with opposite signs of θ SH . When t Ta = 4 nm, the enhanced effective θ SH for Pt/Co/Ta shows a maximum value around 0.356, which is larger than the sum of | θ SH | for Pt and Ta and is ascribed to an additional interfacial SOT at Co/Ta interface. θ SH gradually decreases with increasing Ta layer thickness beyond 4 nm, which can be explained by the improved crystallinity of Ta layer. Our results confirm a way to decrease the switching current density in SOT-based spintronic devices.